“Reach, Benefit, Empower” framework of indicators for monitoring programs and policies incorporated into trainings conducted by partners - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
CGIAR researchers have developed a framework that identifies a need for projects and programs to distinguish between approaches that ‘reach’ women as participants, those that actually ‘benefit’ women and finally those that ‘empower’ them. This Reach, Benefit, Empower (RBE) framework has been published in a journal article and has been used by The Deutsche Gesellschaft für Internationale Zusammenarbeit GmbH (GIZ) and The International Development Research Centre (IDRC) in presentations.